2015
DOI: 10.1111/ejn.12847
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and visual interactions between the superior and inferior colliculi in the ferret

Abstract: The integration of visual and auditory spatial information is important for building an accurate perception of the external world, but the fundamental mechanisms governing such audiovisual interaction have only partially been resolved. The earliest interface between auditory and visual processing pathways is in the midbrain, where the superior (SC) and inferior colliculi (IC) are reciprocally connected in an audiovisual loop. Here, we investigate the mechanisms of audiovisual interaction in the midbrain by rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…While consistent with the possibility that visual updating of the perceived direction of a sound source is based on changes in auditory cortical activity, it is also possible that interactions between visual and auditory inputs in the midbrain may be involved. Reciprocal connections exist between the SC and different regions of the inferior colliculus (IC) (Doubell et al, 2000; Stitt et al, 2015), providing a source of retinotopically organized input into the auditory midbrain. Furthermore, auditory responses in the monkey IC are modulated by changes in gaze direction (Zwiers et al, 2004; Gruters and Groh, 2012), implying a role for the midbrain in coordinating neural representations of auditory and visual space.…”
Section: Discussionmentioning
confidence: 99%
“…While consistent with the possibility that visual updating of the perceived direction of a sound source is based on changes in auditory cortical activity, it is also possible that interactions between visual and auditory inputs in the midbrain may be involved. Reciprocal connections exist between the SC and different regions of the inferior colliculus (IC) (Doubell et al, 2000; Stitt et al, 2015), providing a source of retinotopically organized input into the auditory midbrain. Furthermore, auditory responses in the monkey IC are modulated by changes in gaze direction (Zwiers et al, 2004; Gruters and Groh, 2012), implying a role for the midbrain in coordinating neural representations of auditory and visual space.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrets have been used extensively in physiological and anatomical studies of multisensory processing (e.g. King & Hutchings, 1987;King et al, 1988;King & Schnupp, 2000;Bizley et al, 2007;Bizley & King, 2008;Stitt et al, 2015), but only to a limited degree so far in behavioural experiments (Isaiah et al, 2014;Hollensteiner et al, 2015), despite the ease with which they can be trained to carry out localization and other sensory tasks. We have previously characterized sound localization behaviour in this species by measuring their head-orienting response following stimulus presentation and the subsequent locomotor response as the animals approach the perceived location of the sound source to receive a water reward (Nodal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, anatomical tracings have shown that the inferior colliculus receives visual input from the SC, as well as from retina and visual cortex [ 69 72 ], although a recent study in mouse indicates that retinal projections to the inferior colliculus are sparse [ 39 ]. Furthermore, electrophysiological analyses of the anesthesized ferret suggest that the source of the visual responses in the inferior colliculus is the SC rather than direct input from the retina or cortex [ 73 ]. Therefore, it is unlikely that absence of the inferior colliculus would directly affect RGC numbers and axonal projections to the SC in AP-2δ−/− mice; however, it is highly likely that absence of the inferior colliculus can affect SC response, especially as related to visual and auditory signal integration in midbrain.…”
Section: Discussionmentioning
confidence: 99%